Danhong Injection Reversed Cardiac Abnormality in Brain–Heart Syndrome via Local and Remote β-Adrenergic Receptor Signaling - Orgah, John O.; Yu, Jiahui; Zhao, Tiechan; Wang, Lingyan; Yang, Mingzhu; Zhang, Yan; Fan, Guanwei; Zhu, Yan (Frontiers in Pharmacology, 2018)
Ischemic brain injury impacts cardiac dysfunction depending on the part of the brain affected, with a manifestation of irregular blood pressure, arrhythmia, and heart failure. Generally called brain-heart syndrome in traditional Chinese medicine, few mechanistic understanding and treatment options are available at present. We hypothesize that considering the established efficacy for both ischemic stroke and myocardial infarction (MI), Danhong injection (DHI), a multicomponent Chinese patent medicine, may have a dual pharmacological potential for treating the brain-heart syndrome caused by cerebral ischemic stroke through its multi-targeted mechanisms. We investigated the role of DHI in the setting of brain-heart syndrome and determined the mechanism by which it regulates this process. We induced Ischemia/Reperfusion in Wistar rats and administered intravenous DHI twice daily for 14 days. We assessed the neurological state, infarct volume, CT scan, arterial blood pressure, heart rhythm, and the hemodynamics. We harvested the brain and heart tissues for immunohistochemistry and western blot analyses. Our data show that DHI exerts potent anti-stroke effects (infarct volume reduction: **P < 0.01 and ***P < 0.001 vs. vehicle. Neurological deficit correction: *P < 0.05 and ***P < 0.001 vs. vehicle), and effectively reversed the abnormal arterial pressure (*P < 0.05 vs. vehicle) and heart rhythm (**P < 0.01 vs. vehicle). The phenotype of this brain-heart syndrome is strikingly similar to those of myocardial infarction (MI) model. Quantitative assessment of hemodynamic in cardiac functionality revealed a positive uniformity in the PV-loop after administration with DHI and valsartan in the latter. Immunohistochemistry and western blot results showed the inhibitory effect of DHI on the β-adrenergic pathway as well as protein kinase C epsilon (PKCε) (**P < 0.01 vs. model). Our data showed the underlying mechanisms of the brain-heart interaction and offer the first evidence that DHI targets the adrenergic pathway to modulate cardiac function in the setting of brain-heart syndrome. This study has made a novel discovery for proper application of the multi-target DHI and could serve as a therapeutic option in the setting of brain-heart syndrome.